Kajian Hukum Tata Negara Terhadap Perlindungan Hak Atas Tanah Dalam Konteks UU No. 5 Tahun 1960 - Fakhrurrozi, Muhammad; Rahmatiar, Yuniar; Abas, Muhamad (2025)
The Basic Agrarian Law (UUPA) was born as a response to the need for new agrarian law after the change of power from colonial to the Indonesian national government. UUPA aims to eliminate the legacy of discriminatory colonial law and create a more just and socially just agrarian system. This study aims to analyze the principles contained in Law No. 5 of 1960 concerning the protection of land rights and how the perspective of constitutional law on the protection of land rights according to Law No. 5 of 1960 concerning Basic Agrarian Regulations. This study uses a normative legal approach as the main method. The selection of this approach is intended to examine the construction of laws and regulations, basic legal values, and the views of legal experts in order to formulate solutions to the legal issues analyzed. The results of the study indicate that from the perspective of constitutional law, UUPA has fulfilled the fundamental elements, especially in relation to the principle of Grundnorm or basic norms, which in the Indonesian context refers to Pancasila. UUPA is in line with the constitution, especially Article 33 paragraph (3) of the 1945 Constitution, which emphasizes that the land, water, and natural resources are controlled by the state for the prosperity of the people. As a legal instrument, UUPA plays a role in ensuring justice in the control, utilization, and maintenance of land, especially for marginalized groups. However, despite upholding the values of social justice, equal rights, and legal certainty, the implementation of UUPA still faces various challenges, such as weak law enforcement and protection of vulnerable groups. Therefore, further efforts are needed in agrarian reform to ensure legal support for all Indonesian people in accordance with the basic principles of the state.